The Influence of Marketing and Service Strategies on Loyalty through Customer Satisfaction at ULI OLSHOP Store in North Luwu Regency - Wahid, Abdul; M Anwar, Suhardi; Khaddapi, Muammar (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: The study aims to investigate the influence of marketing strategies and service quality on customer loyalty, using customer satisfaction as a mediating variable at Uli Olshop Store, North Luwu Regency. Methodology: A quantitative approach was used, involving 100 respondents who were customers of Toko Uli Olshop. The data were analyzed using multiple linear regression. Results: The study found that marketing strategies and service quality significantly influence customer loyalty. Marketing strategies do not significantly influence customer satisfaction, while service quality contributes greatly . Customer satisfaction plays an important role in increasing customer loyalty. The coefficient of determination shows that the research model has strong predictive power in explaining the relationship between variables. Findings: Service quality is the dominant factor influencing customer satisfaction, while marketing strategies are more effective at directly influencing loyalty than customer satisfaction. Novelty: This study integrates customer satisfaction as a mediating variable to examine the relationship between marketing strategy, service quality, and customer loyalty in the context of local online stores, which has rarely been studied in small businesses in rural areas. Originality: This study examines a specific case of local e-commerce in North Luwu Regency, providing empirical evidence for the literature on digital marketing and service quality in regional markets. Conclusion: Improving service quality must be a priority to increase customer satisfaction and loyalty, while effective marketing strategies need to be maintained to strengthen loyalty directly. Type of Paper: Empirical Research Article